An electronic questionnaire for liver assessment in congenital disorders of glycosylation (LeQCDG): A patient-centered study - Marques-da-Silva, Dorinda (2020)
Dorinda Marques-da-Silva acknowledges the support from the Rare Disease Foundation’s microgrant and ‘Liliana Scientific Scholarship’; Rita Francisco acknowledges Fundação para a Ciência e Tecnologia for the grant SFRH/BD/124326/2016 awarded to her.